THE IMPROVEMENT OF COMMUNICATION AND INFERENCE SKILLS IN COLLOID SYSTEM MATERIAL BY PROBLEM SOLVING LEARNING MODEL - yunita maisarera; chansyanah diawati; noor fadiawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is to describe the effectiveness of problem solving learning in improving communication and inference skills in colloid system material.  Subjects in this research were students of XIIPA1 and XI IPA2 classrooms in Persada Junior High School in Bandar Lampung in academic year 2011-2012 where students of both classrooms had the same characteristics. This research used quasi experiment method and pretest-posttest control group design. Effectiveness of problem solving learning method was measured based in n-gain value. The results showed that average n-gain values of communication and inference skills were 0.28 and 0.31 respectively. It could be concluded that the problem solvinglearning in colloid system material was effective in improving inferring skill with high category and communication skill with medium criterion.Keywords       : problem solving learning, communication and inference skills